DEVELOPMENT MIND MAP LEARNING MEDIA FOR APPLICATION-ASSISTED ENGLISH COURSES - Juita, Nelya; Sunarhati, Marliyus; Anggrainy, Rita; Zulaikah (LPPM STBA Pontianak, 2024)
In classroom learning activities, the presence of media is essential to pay attention to. If selected and used according to class conditions, various alternative uses of learning media will provide optimal results. This research aims to develop learning media using the Freemind application in English courses to produce learning media that is valid, practical, and has potential effects. The results obtained from the development stages carried out by researchers showed that the mind map media with the developed Freemind application was declared to have proven its practicality. The score of learning outcomes for English courses in the medium category determined the effectiveness of the mind map media with the Freemind application. This was based on The results of calculating the N gain value in material 1, which was 0.4708 (effective in the medium category), and the calculation of N gain was 0.4882 in material 2 (effective in the medium category), so the average score was 0.4795. However, the basic comparisons used as research material in this study were only obtained from 2 materials.